A New Species of Pachysentis Meyer, 1931 (Acanthocephala: Oligacanthorhynchidae) in the Brown-Nosed Coati Nasua nasua (Carnivora: Procyonidae) from Brazil, with Notes on the Genus and a Key to Species - Gomes, Ana Paula N.; Amin, Omar M.; Olifiers, Natalie; Bianchi, Rita de Cassia [UNESP]; Souza, Joyce G. R.; Barbosa, Helene S.; Maldonado, Arnaldo (Springer, 2019)
Introduction Pachysentis comprises 10 species, which have been reported parasitizing mammals in Africa and the American continent. However, species of Pachysentis have not been described in brow-nosed coatis. Pachysentis lauroi n. sp. (Oligacanthorhynchidae: Acanthocephala) is described from the brown-nosed coati Nasua nasua (Linnaeus, 1766) Storr, 1780 (Procyonidae: Carnivora) in the Brazilian Pantanal wetlands of the Mato Grosso do Sul State, Brazil. Methods Specimens were studied using light and scanning electron microscopy. Result The new species is distinguished from other species of Pachysentis by the number of hooks in each longitudinal row (12 rows of 4 hooks, total of 48 hooks), presence of barbs on all hooks, and the organization of the cement glands. Notes on the genus Pachysentis [14] and a key to its species are provided. Critical comments on some species with a dubious diagnosis and questionable or missed key taxonomic characteristics are also reviewed. We also discuss the zoogeography of the members of the genus.
Keywords: Acanthocephala; Pachysentis lauroi n; sp; Key to species; Carnivore; Mato Grosso do Sul; Brazil